Severity of Factors Resisting Implementation of Inclusive Education: A Survey of Public-School Teachers’ Perceptions - Muhammad Usman Zia, Adnan Ahmad, Farhan Sarwa (JIE, 2024)
Given Pakistan's lagging progress in fulfilling its international commitments to educate children with disabilities, inclusive education emerges as the sole tenable solution. This study, employing a descriptive design and survey methodology, delves into the perspectives of regular public-school teachers, recognized as key stakeholders in this pivotal transition. The findings reveal a constellation of interconnected factors impeding successful implementation: insufficient awareness and training among teachers, inaccessible school environments, entrenched social stigmas, negative attitudes, resource limitations, and inadequacies in inclusive curriculum and instruction. Addressing these challenges necessitates a multifaceted approach encompassing comprehensive awareness campaigns, infrastructural upgrades, targeted teacher training programs, strategic resource mobilization, and proactive community engagement.